1994
DOI: 10.1007/bf01972001
|View full text |Cite
|
Sign up to set email alerts
|

Role of serological tests in the diagnosis of immune complex disease in infection of ventriculoatrial shunts for hydrocephalus

Abstract: Seven cases of ventriculoatrial shunt infection with immune complex disease are reported in order to demonstrate the usefulness of measurement of levels of specific antibody to Staphylococcus epidermidis in diagnosis. Blood and cerebrospinal fluid cultures gave misleading results, and there was initial doubt about the diagnosis in all seven cases. All showed grossly elevated titres of antibody to Staphylococcus epidermidis, with raised serum C-reactive protein levels and depressed complement levels. Measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The low complements, as discussed previously, may represent activation of the classical pathway as the disease unfolds [69]. For disease screening and diagnostic purposes, Bayston et al have proposed the use of Anti Staphylococcus Epidermidis Titer (ASET) after they demonstrated that ASET rises predictably in patients with VA shunts colonized by Staphylococcus epidermidis [61, 76, 77]. While the ASET is a welcome addition to the diagnostic armamentarium, no single symptom, sign, or lab finding should be considered in isolation when shunt nephritis is suspected.…”
Section: Discussionmentioning
confidence: 99%
“…The low complements, as discussed previously, may represent activation of the classical pathway as the disease unfolds [69]. For disease screening and diagnostic purposes, Bayston et al have proposed the use of Anti Staphylococcus Epidermidis Titer (ASET) after they demonstrated that ASET rises predictably in patients with VA shunts colonized by Staphylococcus epidermidis [61, 76, 77]. While the ASET is a welcome addition to the diagnostic armamentarium, no single symptom, sign, or lab finding should be considered in isolation when shunt nephritis is suspected.…”
Section: Discussionmentioning
confidence: 99%
“…Blood culture is also of limited value, except for cases of vascular shunts, where it is positive in up to 90% of infections [6]. The level of specific antibodies against Staphylococcus epidermidis is also a useful alternative for the diagnosis of chronic ventriculoatrial shunt-related infections [62]. Abdominal ultrasound may be helpful in the identification of CSF collections.…”
Section: Diagnosismentioning
confidence: 99%
“…We made this shift because VA shunts have been associated with infrequent yet potentially catastrophic complications. These included endocarditis/atrial thrombi [11], immune complex disease [12] and shunt nephritis [13]. Essentially, a VA shunt is a chronic indwelling intravascular foreign body, and even low-grade infection will produce chronic bacteremia.…”
Section: Discussionmentioning
confidence: 99%